“Desarrollo de una aplicación web para el agendamiento de citas y manejo de historial médico de la Unidad Médica Alejandro del cantón La Maná”. - Ibarbo Espinoza, Joselyne Elizabeth (2023)
In recent years, information systems have gained presence in different fields, these ones can be areas of agriculture, business, industry, and health. This last field has ventured into telemedicine, medical appointment scheduling, medical history, and generation of medical prescriptions, but the lack of dissemination of a system has generated little use of applications that help to optimize medical administrative processes. The aforementioned is used as a basis to consider as objective the development of a web application using the agile Scrum methodology for the scheduling of medical appointments and medical history in the Alejandro Medical Unit. To meet the objective, bibliographic and field research methods are applied, which allowed knowing the problem and establishing research techniques such as the survey and interview. In turn to this and using the Scrum development methodology, user stories, design, coding, and tests were obtained. As a result, a quality software product was obtained for scheduling appointments by the patient and history management by the doctor with notification, reminder, and report parameters. Finally, it can be concluded that the developed software will run on different internet browsers and operating systems of computers and mobile devices.